2020
DOI: 10.1074/jbc.ra118.007212
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 6 deficiency transcriptionally up-regulates TGF-β signaling and induces fibrosis in mice

Abstract: Caloric restriction has been associated with increased life span and reduced aging-related disorders and reduces fibrosis in several diseases. Fibrosis is characterized by deposition of excess fibrous material in tissues and organs and is caused by aging, chronic stress, injury, or disease. Myofibroblasts are fibroblast-like cells that secrete high levels of extracellular matrix proteins, resulting in fibrosis. Histological studies have identified many-fold increases of myofibroblasts in aged organs where myof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 67 publications
2
41
0
1
Order By: Relevance
“…First, in the present study, we have observed significant reduction in protein expressions of Sirt1, Sirt3, and Sirt6 in the DM+PBS group, except Sirt2, compared with the control rats. This observation might support the hypothesis that Sirt1, Sirt3, and Sirt6 could play an important role in the development of tissue fibrosis induced by diabetes, which is consistent with previous research results [24,41,42] and Sirt2 might not participate in this process. Administration of MSCs results in a significant increase in Sirt3 protein expressions but fails to upregulate the protein expressions of Sirt1 and Sirt6, suggesting that the protective effect of MSCs against diabetic lung fibrosis may be sirt3-dependent, which may be related to the paracrine effects of MSCs [84], but the specific mechanism is not clear.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 93%
See 1 more Smart Citation
“…First, in the present study, we have observed significant reduction in protein expressions of Sirt1, Sirt3, and Sirt6 in the DM+PBS group, except Sirt2, compared with the control rats. This observation might support the hypothesis that Sirt1, Sirt3, and Sirt6 could play an important role in the development of tissue fibrosis induced by diabetes, which is consistent with previous research results [24,41,42] and Sirt2 might not participate in this process. Administration of MSCs results in a significant increase in Sirt3 protein expressions but fails to upregulate the protein expressions of Sirt1 and Sirt6, suggesting that the protective effect of MSCs against diabetic lung fibrosis may be sirt3-dependent, which may be related to the paracrine effects of MSCs [84], but the specific mechanism is not clear.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 93%
“…MSCs Activate the Sirt3/SOD2 Signaling Pathway. It is well known that the sirtuin family is composed of seven members (Sirt1 to Sirt7), out of which Sirt1, Sirt2, Sirt3, and Sirt6 exert positive effects on tissue fibrosis, especially Sirt3 [41,42]. To investigate the mechanisms of MSCs against diabetes-induced lung fibrosis, we hypothesized that the capability of MSCs might mainly result from upregulating the Sirt3/SOD2 signaling pathway.…”
Section: Mscs Inhibit Epithelial-mesenchymal Transition Andmentioning
confidence: 99%
“…TGF-β signaling has been reported to be dysregulated in IBD patients, and its impairment results in spontaneous colitis in mouse model [ 31 ]. SIRT6 could bind to and repress the expression of key TGF-β genes to decrease the activation of TGF-β signaling [ 32 ]. We speculate that TAK1, as an important component of TGF-β signaling, whose activation is to be suppressed by inhibited TGF-β signaling regulated by SIRT6 [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 could bind to and repress the expression of key TGF-β genes to decrease the activation of TGF-β signaling [ 32 ]. We speculate that TAK1, as an important component of TGF-β signaling, whose activation is to be suppressed by inhibited TGF-β signaling regulated by SIRT6 [ 31 , 32 ]. This still requires further research to prove.…”
Section: Discussionmentioning
confidence: 99%
“…Research progress over the past few years has described critical roles for SIRT6 in DNA repair, metabolic regulation, tumor suppression, and longevity (179,180). Given these biological roles, SIRT6 has emerged as a candidate for small molecule activation to extend lifespan through the treatment or prevention of age-associated disease, including nonalcoholic fatty liver disease, cancer, fibrosis, and cardiac hypertrophy (52,(181)(182)(183). Early work demonstrated the ability of SIRT6 to be activated in vitro by various small molecules, including free fatty acids and natural products (25,115,147,152).…”
Section: Perspectivementioning
confidence: 99%